Effect of ion exchange resins on white and red wine pH: impact on wine sensory characteristics - Borges, Rita (2019)
The pH control during winemaking is a fundamental parameter by their influence on color, freshness and to achieve wine microbiological stability. The most common acidify correction performed in wineries is addition of natural tartaric acid; however, in some cases, this operation increases the risks of potassium bitartrate precipitations [1, 2]. The application of ion exchange resins for wine acidification is based on ability of exchanging ions fixed on functional groups, namely by exchanging cations, such as potassium, with hydrogen ions. Nevertheless, there is an important lack of knowledge on the impact of this operation on wine sensory characteristics. To adjust wine pH, a certain amount of treated wine by ion exchange resins is mixed with the untreated wine [3]. According to OIV [4], treatment must not lower the pH of wine below 3.0 and the decrease should not exceed 0.3 pH units. Anion exchangers are not allowed by the OIV [3] due to the negative effects on the wine sensory quality [5,6]. Therefore, the aim of this work was to evaluate the effect of cation exchange resins, authorized by the OIV, according to Resolution 43/2000 [3] on wine pH control and to evaluate their impact on wine sensory quality at industrial scale. In this study a white and a red wine from the Douro Valley region, 2015 vintage, was used. In this work ion exchange resin treated white wine was almost 20% from total white wine volume and red wine was almost 30% from total red wine volume. The present study indicated that there were no considerable changes in sensory attributes, although a slight improvement in the aroma and taste, as a result of the ion-exchange pH adjustment. These results show that the application of ion exchange resins process to wine could be an interesting tool for white and red wine pH adjustment, without interfering with wine sensorial quality.